Preclinical Evaluation of Fingolimod in Rodent Models of Stroke With Age or Atherosclerosis as Comorbidities - Diaz Diaz, Andrea C.; Malone, Kyle; Shearer, Jennifer A.; Moore, Anne C.; Waeber, Christian (Frontiers in Pharmacology, 2022)
Preclinical data indicate that fingolimod improves outcome post-ischaemia. This study, used a rigorous study design in normal male C57BL/6JOlaHsd mice and in mice with common stroke comorbidities to further evaluate the translational potential of fingolimod. Materials and methods: Stroke was induced via middle cerebral artery electrocoagulation in 8-10-week old mice (young mice), 16-month old mice (aged mice), and in high-fat diet-fed 22-week old ApoE-/- mice (hyperlipidaemic mice). Recovery was evaluated using motor behavioural tests 3 and 7 days after stroke. Tissue damage was evaluated at 7 days. A lower dose of fingolimod, 0.5mg/kg, but not 1mg/kg, increased lesion size but decreased ipsilateral brain atrophy in younger mice, without an effect on behavioural outcomes. Fingolimod-treated aged mice showed a significant improvement over saline-treated mice in the foot fault test at 7 days. Fingolimod-treated hyperlipidaemic mice showed a decreased infarct size but no difference in behavioural performance. Increasing fingolimod treatment time to 10 days showed no benefit in young mice. Pooled data showed that fingolimod improved performance in the foot fault test. Flow cytometry studies showed that fingolimod had marked effects on T cell frequencies in various tissues. The results show that the effects of fingolimod in stroke are less robust than the existing literature might indicate and may depend on the inflammatory status of the animals.